METHOD OF ASSESSING THE LEVEL OF FINANCIAL SECURITYENTERPRISES OF THE HOTEL INDUSTRY - CHEBAN, TETYANA; ZAITSEVA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the methods of assessing the level of financial security of hotel enterprises. Based on the generalization of research on the methodology of the main approaches to assessing the financial security of enterprises, the authors systematized the advantages of the indicator method: the objectivity of the results based on quantitative assessments of indicators; the ability to quickly monitor negative trends in the enterprise; simplicity of calculations; coverage of various spheres of activity of enterprises; availability of objective information presented in openly published financial statements of enterprises; low time cost and no need for deep special skills for practical application.It is established that the use of the indicator method involves the solution of certain methodological problems, the main of which is the adaptation of normative values of indicators to the specifics of the hotel industry. Given the solution of this problem, the use of the indicator method to assess the level of financial security of hotel enterprises is quite justified and appropriate.Determining the industry characteristics of the hotel industry, which affect the limit values of indicators of the group of financial stability indicators, allowed to offer the use of individual standards for the group of financial stability indicators, namely the coefficient of autonomy, financial leverage, manоeuvrability of equity, current assets and working capital their limit values. For the purpose of practical approbation of the offered technique the comparative analysis of integral indicators of financial stability of the hotel enterprise under classical and author's approaches is carried out.The obtained results prove that the proposed model allows to obtain a more substantiated partial and aggregate integrated assessment of the level of financial security of the hotel enterprise, as it takes into account industry specifics of the hospitality industry, in terms of factors influencing capital structure optimization. The use of the author's approach will help to improve the methodological support of financial security management of the hotel industry.
Keywords: financial security; evaluation methods; hotel industry; enterprises